HUBUNGAN ANTARA PENERIMAAN DIRI DAN DUKUNGAN SOSIAL ORANG TUA ANAK AUTIS DENGAN INTERAKSI SOSIAL ANAK AUTIS - suyanti suyanti; Kurniyatul Faizah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2019)
This study aims to determine how much influence social acceptance and support for parents of autistic children with social interaction of children with autism. The population is 30 parents of autistic children and the closestpeople who attend in PAUD Inklusi Anggrek MandiriSitubondo and the sample is the whole of the population of some 30 people. This study is correlational; the subject is determined by purposive sampling technique. Results of the study showed that the regression analysis coefficient on F = 17.839, p = 0.000 (p <0.05) so that there is a significant relationship between self-acceptance and social support for parents of autistic children with social l interactionautistic children is received. Partially there is a significant correlation between self-acceptance with social interaction shown by prices at t = 5.018, p = 0.000, so the hypothesis is accepted. In parsal also shown at t = 1.613 p = 0.118 (p> 0.05), so the research hypothesis that says there is a relationship of social support with social interaction rejected. So overall derived price Sguare R = 0.569 which shows variable acceptance of self and social support contributed 56.9% effective this further strengthensacceptance your self parents with autistic children and social support autistic children associated with autistic children social interaction. So H0 rejected, which means acceptance of self and relationship betweensocial parents support correlated with sociall interactionautistic children.